Nitrobenzodiazepines: Postmortem brain and blood reference concentrations. (November 2016) - Skov, Louise; Holm, Karen Marie Dollerup; Linnet, Kristian
Highlights: Postmortem brain and blood reference concentrations were established. A positive correlation between brain and blood concentrations was found. Brain–blood ratios were independent of concentration level. Brain is a useful postmortem specimen due to the low pre-analytical variation. Poisonings occurred mainly as polydrug cases rather than single-drug intoxications Abstract: Reference concentrations are needed to evaluate postmortem toxicology results and usually femoral blood is the specimen of choice. However, brain tissue has been suggested as a viable alternative specimen, since postmortem blood concentrations can be difficult to interpret due to postmortem redistribution, among other factors. Here we present reference concentrations of postmortem brain and femoral blood of the nitrobenzodiazepines clonazepam, flunitrazepam, and nitrazepam that are of particular interest since they commonly are converted to their corresponding 7-aminometabolites in the postmortem situation. The drugs and metabolites were quantified in both matrices using LC–MS-MS in 69 cases. In 63 cases the compounds were judged not to have been of significance for the death (C cases), whereas they were considered to have been a contributing factor in 6 cases (B cases). No cases were observed with a nitrobenzodiazepine being the sole cause of death (A cases). The brain–blood ratios for clonazepam and nitrazepam were 5.5 and 4.7, respectively, while the brain–blood ratios for the 7-aminometabolites ranged from 0.4 to 0.5. Flunitrazepam only occurred as the 7-aminometabolite. A positive correlation between brain and blood concentrations was found with Spearman's rank correlation coefficients ( r s ) ranging from 0.77 to 0.96. The measured femoral blood concentrations agree with literature values, but only few brain concentrations were available for comparison. The drug–metabolite ratios for clonazepam and nitrazepam were 10–12 times higher in brain than in blood. The pre-analytical variation in brain of 5.9% was fairly low, suggesting that brain tissue is a useful alternative to blood. The reported brain and femoral blood concentrations serve as reference values in postmortem investigations.